2017
DOI: 10.1103/physrevlett.119.256101
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous Tensile Detwinning in Twinned Nanowires

Abstract: In spite of numerous studies on mechanical behaviors of nanowires (NWs) focusing on the surface effect, there is still a general lack of understanding on how the internal microstructure of NWs influences their deformation mechanisms. Here, using quantitative in situ transmission electron microscopy based nanomechanical testing and molecular dynamics simulations, we report a transition of the deformation mechanism from localized dislocation slip to delocalized plasticity via an anomalous tensile detwinning mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 43 publications
(46 reference statements)
5
49
0
Order By: Relevance
“…This specific hardening behavior was also observed in the five-fold NT Ag nanowires [ 22 ]. Moreover, the obvious strengthening effect by CTBs is found and enhances with the decrease in the twin spacing, as shown in Figure 2 a,b, which has been widely reported and well understood in literatures [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…This specific hardening behavior was also observed in the five-fold NT Ag nanowires [ 22 ]. Moreover, the obvious strengthening effect by CTBs is found and enhances with the decrease in the twin spacing, as shown in Figure 2 a,b, which has been widely reported and well understood in literatures [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 61%
“…An attractive strategy is engineering coherent twin boundaries (CTBs) with nanometer-scale spacing into nanowires, i.e., nanotwinned nanowires (NT nanowires). Several NT nanowires are founded to exhibit extreme-high strength and even ideal strength, such as NT Cu [ 13 , 14 , 15 ], Ni [ 16 , 17 ], Au [ 8 , 18 , 19 ], Ag [ 20 , 21 ], and Al [ 21 ]. Interestingly, the desired strain hardening capability can be rebuilt in low stacking-fault energy metals nanowires, such as NT Au and NT Ag nanowires containing orthogonally oriented CTBs [ 21 , 22 ] and fivefold vertical CTBs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In <110> loading direction, a high density of sessile dislocation networks formed at the twin boundary, while in <112> loading direction, a lower density of glissile dislocation networks was observed [19]. In nanopillar containing a single axial twin boundary, Cheng et al [20] reported the complete annihilation of twin boundary leading to the formation of a single crystal, which has been attributed to anomalous de-twinning mechanism. However, the influence of twin boundary spacing has not been investigated when the twin boundaries are parallel to the loading direction.…”
Section: Introductionmentioning
confidence: 99%
“…Metallic nanowires are promising building blocks for a host of applications such as transparent electrodes, sensors, flexible or stretchable electronics, etc. [1][2][3][4][5][6][7]. The operation and reliability of nanowires-based devices call for a robust mechanical performance and a thorough understanding of their deformation behaviors.…”
Section: Introductionmentioning
confidence: 99%